Material Degradation Due to Erosion and Preventive Measures - Singh, Balwinder; Kumar, Pardeep; Sidhu, Hazoor Singh (Asian Journal of Engineering and Applied Technology, 2016)
In industrial applications, surface of different equipments are damaged by solid particles entrained in a fluid stream. This type of wear is generally characterized as erosion. Probably the most considerable erosion problems which found in industry are those connected with the equipment used such as in coal-fired power plants, hydraulic turbines, fluid-bed system and coal purification plants etc. Erosion may come into play, when the moving particles strike-out the material from the surface of the equipment which reduces the life and efficiency of the plant equipments. The various factors named as particle shape, particle velocity, angle of impingement and properties of target material, affect the erosion rate. Hardfacing is one of simple and most effective technique to increase the erosion resistance by different welding processes. The soft surface of the component is deposited by suitable alloys or composites which enhance the surface properties. Hardfacing is a useful technique for either repair of failed components or manufacturing of new components.